Audiological Outcomes of Stapedotomy: Our Experience - Pradhananga, R.; Nair, G.; Sapathkumar, R.; Kameswaran, M. (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Objective: This study was aimed to sequentially document the patient’s audiological improvement after stapedotomy as measured by pure tone audiometry.Material and Methods: This prospective clinical study was performed in a total of 100 patients (age range: 20 – 63 years), diagnosed with Otosclerosis who underwent Stapedotomy at the Department of Otology, Madras ENT Research Foundation, Chennai between September 2010 to March 2012. Pre-operative and Post-operative audiometric evaluation was done using the same conventional pure tone audiometer with standard calibrations. Post-operative audiometry was sequentially performed at 6 months, 1 year and 2 years. Bone-conduction and air conduction thresholds and the Air-bone gap (ABG), were assessed at each schedule at 0.5 KHz, 1 KHz, 2 KHz and 4 KHz frequencies respectively.Result: All patients had significant audiological improvement as measured by their sequential pure tone audiometries. Overall, the frequency specific pre-operative mean average Air-Bone gap was 52.3dB at 500Hz, 36.5dB at 1KHz, 39.3dB at 2KHz, 38.7dB at 4KHz and the frequency specific postoperative mean average Air-Bone Gap closure was achieved by 27.8dB at 500Hz, 29.6dB at 1KHz, 13.6dB at 2KHz, 11.4dB at 4KHz, by the time of 2 years of follow up. A successful closure of AB gap >10dB was achieved in these speech frequencies in 80% of cases. The frequency specific bone-conduction thresholds were unchanged postoperatively. Two patients developed post-operative vertigo, out of which 1 developed SNHL after 3 weeks of surgery.Conclusion: The study confirms that stapedotomy is a safe and successful procedure in the hands of a well trained otologist, providing long-term hearing improvement to patients with otosclerosis.